ON THE NON-RANDOM DISTRIBUTION OF EDUCATIONAL DEPRIVATION OF CHILDREN IN INDIA - Motkuri Venkatanarayana (Centre for Development Studies-WP372, 2005)
The emphasis on education assumes importance given the recent recognition of human capital, human rights and human development perspectives of development. Hence educational deprivation is recognised as the primary agent of human deprivation and all necessary measures are required to ensure minimum education for every child. Such a universal recognition emanates from the given magnitude of educationally deprived children all around the world. On this premise, this is an attempt at examining the levels and inequities associated with the phenomenon of educational deprivation of children during 1990's in India. This exercise provides a detailed exposition of the household characteristics of the deprived children based on information obtained in National Sample Survey Organisation (NSSO). The persistence of educational deprivation among children in India is due to socio-economic deprivation in general; however, it remains debatable but whether the remedy lies in making the schooling provision universal. This paper argues that the provision may be necessary but not a sufficient condition to accomplish the dream goal of universal elementary education. Alternatively it argues for a greater role of the state to ensure the enabling conditions in the household domain; in other words, the state has the responsibility of ensuring the well-being of all children on an equal footing. The state's responsibility is of equal importance of that of the parents.